Mediterranean-Oriented Dietary Intervention Is Effective to Reduce Liver Steatosis in Patients with Nonalcoholic Fatty Liver Disease: Results from an Italian Clinical Trial - Barbara Zanini; Federica Benini; Monica Marullo; Anna Simonetto; Angelo Rossi; Paola Cavagnoli; Alessia Bonalumi; Silvia Marconi; Marie Graciella Pigozzi; Gianni Gilioli; Alessandra Valerio; Francesco Donato; et al. (International Journal of Clinical Practice)
Background of the Study. Nonalcoholic fatty liver disease (NAFLD) is the most common liver disease in western countries. Lifestyle interventions are recommended as the primary therapy for NAFLD. Methodology. In this clinical trial, NAFLD patients were enrolled in a 12-month dietary intervention aimed to improve their eating habits according to the Mediterranean pattern, with scheduled appointments every three months. After the exclusion of steatosis, healthy subjects were recruited and received general advice based on current Italian food-based dietary guidelines. Results. One hundred and fifty five subjects aged 20–59 years underwent (i) liver ultrasound (US), (ii) clinical and anthropometric evaluations, (iii) blood tests, and (iv) assessment of dietary habits. According to US evaluation, 73 of them had severe, moderate, or mild liver steatosis (NAFLD patients) and 82 had no liver steatosis (healthy controls). Fifty-eight NAFLD patients and 73 controls completed the study. Among NAFLD patients, 26 (45%) downgraded steatosis severity, 12 of which achieved complete steatosis regression (21%). Three of the healthy controls developed NAFLD. The NAFLD patients improved their dietary habits and reduced BMI and waist circumference, during the study period, more than healthy controls. Liver steatosis remission/regression was independent of changes in BMI or liver enzymes and was more frequent among patients with mild steatosis at baseline. Conclusions. Mediterranean dietary advices, without a personalised meal planning, were efficient in reducing/remitting NAFLD, especially among patients with mild disease, which argues in favour of early identification and lifestyle intervention. This trial is registered with NCT03300661.